2017
DOI: 10.1038/ncomms14457
|View full text |Cite
|
Sign up to set email alerts
|

Selective sulfur dioxide adsorption on crystal defect sites on an isoreticular metal organic framework series

Abstract: The widespread emissions of toxic gases from fossil fuel combustion represent major welfare risks. Here we report the improvement of the selective sulfur dioxide capture from flue gas emissions of isoreticular nickel pyrazolate metal organic frameworks through the sequential introduction of missing-linker defects and extra-framework barium cations. The results and feasibility of the defect pore engineering carried out are quantified through a combination of dynamic adsorption experiments, X-ray diffraction, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 41 publications
0
97
0
2
Order By: Relevance
“…Another important aspect in this context is the adsorption and capture of hzardous gases using porous materials. For instance, Rodiguez‐Albelo et al reported on the selective adsorption of sulfur dioxide using [Ni 8 (OH) 4 (H 2 O) 2 (BDP_X) 6 ] (H 2 BDP_X = 1,4‐bis(pyrazol‐4‐yl)benzene‐4‐X with X =H (1), OH (2), NH 2 (3)) frameworks . Defects were postsynthetically introduced via etching the respective MOFs with KOH solution, whereby certain amounts of linkers were replaced by OH groups.…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…Another important aspect in this context is the adsorption and capture of hzardous gases using porous materials. For instance, Rodiguez‐Albelo et al reported on the selective adsorption of sulfur dioxide using [Ni 8 (OH) 4 (H 2 O) 2 (BDP_X) 6 ] (H 2 BDP_X = 1,4‐bis(pyrazol‐4‐yl)benzene‐4‐X with X =H (1), OH (2), NH 2 (3)) frameworks . Defects were postsynthetically introduced via etching the respective MOFs with KOH solution, whereby certain amounts of linkers were replaced by OH groups.…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…Navarro's group has reported as eries of Ni MOFs based on 1D chain-like inorganic second building blocks (SBUs) and functionalized H 2 BDP-X (X = NO 2 ,N H 2 ,O H, and SO 3 H), which show remarkable stability and adsorption selectivity for CO 2 over CH 4 or N 2 .F ollowing that work, functionalizedN i-BDP-X MOFs (X = H, OH, and NH 2 )w ere investigated, which exhibited good selective adsorption for SO 2 and CO 2 over N 2 . [12] Recently, we also studied the gasa dsorption of BUT-31, whichw as constructed from an aldehyde-functionalized ligand (H 2 BDP-CHO) and Zn 2 + .B UT-31 shows high structural stabilityi nw ater,e ven up to 100 8C, as well as in highly basic aqueous solution. [13] Along with our research into the construction of pyrazolate MOFs in recent years, and encouraged by the above-mentioned examples of ligand functionalization for tuning the properties of the resulting MOFs, in this work, three functional groups (CHO, CN, and COOH)w erei ntroducedi ntot he backbone of H 2 BDP to build the corresponding Ni-BDP-X MOFs.I nterestingly,the resultingmaterials exhibit not only good stability but also tunable CO 2 adsorption selectivity over N 2 andC H 4 , and protonconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Recently, we also studied the gasa dsorption of BUT-31, whichw as constructed from an aldehyde-functionalized ligand (H 2 BDP-CHO) and Zn 2 + .B UT-31 shows high structural stabilityi nw ater,e ven up to 100 8C, as well as in highly basic aqueous solution. [13] Along with our research into the construction of pyrazolate MOFs in recent years, and encouraged by the above-mentioned examples of ligand functionalization for tuning the properties of the resulting MOFs, in this work, three functional groups (CHO, CN, and COOH)w erei ntroducedi ntot he backbone of H 2 BDP to build the corresponding Ni-BDP-X MOFs.I nterestingly,the resultingmaterials exhibit not only good stability but also tunable CO 2 adsorption selectivity over N 2 andC H 4 , and protonconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…introduced potassium ions into the [Ni 8 (OH) 4 (H 2 O) 2 (BDP_X) 6 ] MOF (H 2 BDP_X=1,4‐bis(pyrazol‐4‐yl)benzene‐4‐X with X=H, OH, NH 2 ) by generating defect sites after immersing the MOF in KOH ethanolic solutions . Furthermore, they showed that the extra‐framework K + ions might be replaced by Ba 2+ ions, resulting in a material with improved affinity for the capture of SO 2 . Other examples of extra‐framework metal cation incorporation include the exchange of the dimethylammonium ions present in the pores of bio‐MOF‐1 by lanthanide ions .…”
Section: Post‐synthetic Metal Exchangementioning
confidence: 99%